Development of the marine protected area network in the Argentine Islands area (Akademik Vernadsky Antarctic Station, Ukraine) - A. Yu. Utevsky; M. Yu. Kolesnykova; D. V. Shmyrov; O. I. Sinna (Ukrainian Antarctic Journal, 2014)
Based on underwater observations the establishment of marine protected areas in the Stella Creek and Skua Creek straits were proposed. Selection of areas was carried out in accordance with the protocol NAGISA and acoustic bottom survey of the Argentine Islands water area. Descriptions of the marine protected areas were developed and their categories according to IUCN methodology were defined. Сompliance indices calculated according to the IUCN methodology assign the Stella Creek and the Skua Creek MPAs to the IUCN protected categories Ia and III, respectively. 3D models of the marine protected areas were designed.